Development of Islamic Thought in Reading Islamic Texts: A Conceptual Study of Literacy Textual-Normative and Contextual-Historical - Arditya Prayogi; Dimas Prasetya (Al-Widad, 2023)
This article aims to describe how the conceptual view of Islamic thought is in reading Islamic texts, especially reading the Qur'an. This is because there are various terms that are introduced but basically it boils down to two approaches in reading Islamic texts. This article was written using a qualitative descriptive approach using the literature study method. From the results of the discussion it is known that various terms of approach in reading Islamic texts actually lead to textual-normative and contextual-historical approaches. The textual-normative approach necessitates a literal reading of the text. This textual-normative approach is then considered unable to answer some human problems in accordance with the times so that the contextual-historical approach appears as an answer to this inability.